2021
DOI: 10.1590/0366-69132021673833121
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic decolorization of an azo dye employing TiO2 anatase/brookite compounds obtained by hydrothermal methods

Abstract: Titanium dioxide is a widely studied material with well-known applications for anatase and rutile phases. Moreover, brookite, another polymorph, which is more difficult to obtain, has caught scientific community interest, especially for photocatalysis applications. Among many methodologies for TiO 2 synthesis, the hydrothermal method stands out, with the possibility of controlling different parameters that lead to a specific phase composition, allowing selective polymorphic obtainment. This method was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…It is important to mention that such a comprehensive study has not yet been performed on Na 2 Ti 6 O 13 . A previous study by our research group 19 indicated that some synthesis conditions used to prepare TiO 2 , for instance, by a microwave-assisted hydrothermal method, favor the formation of anatase and brookite phases. At the same time, other samples were amorphous after synthesis, especially those synthesized with sodium acetate trihydrate or low thermal treatment temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to mention that such a comprehensive study has not yet been performed on Na 2 Ti 6 O 13 . A previous study by our research group 19 indicated that some synthesis conditions used to prepare TiO 2 , for instance, by a microwave-assisted hydrothermal method, favor the formation of anatase and brookite phases. At the same time, other samples were amorphous after synthesis, especially those synthesized with sodium acetate trihydrate or low thermal treatment temperature.…”
Section: Introductionmentioning
confidence: 99%